The Role of Business Communication in Facing Digital Disruption: Adaptation and Innovation Strategies in the Era of Technological Transformation - Nazhala Hairunisya; Saprida Saprida; Havis Aravik; Fadilla Fadilla (Penerbit dan Percetakan CV. Picmotiv, 2025)
The rapid development of digital technology has led to significant disruption in business communication, requiring companies to adapt quickly and innovatively. This study aims to analyze the role of business communication in addressing digital disruption, as well as the adaptation and innovation strategies in the era of technological transformation. The research employs a qualitative approach using library research, with content analysis of relevant academic sources. The findings indicate that the shift from conventional to digital communication enables faster, more open, and interactive engagement between companies and consumers. In addition, changes in consumer behavior, which have become more critical and information-driven, demand more transparent, responsive, and customer-oriented communication. The use of digital media, creative content, and technologies such as big data plays a crucial role in enhancing communication effectiveness. Therefore, adaptive and innovative business communication is essential for improving competitiveness in the digital disruption era.